Analisis Tipe Dan Bidang Gelincir Longsor Di Kabupaten Gorontalo Utara - La Ode Juni Akbar; Fitryane Lihawa; Marike Mahmud (Universitas Negeri Gorontalo, 2021)
The purpose of this study was to determine the type of landslides and analyze the landslide slip in North Gorontalo District, Gorontalo Province using the geoelectric method. This research begins by determining the type and kind of landslides found in the North Gorontalo District. The location of the measurement was carried out at 4 (four) locations, 1st Track in Tomilito District; 2nd track in Sumalata District; 3rd track in Monano District; and 4th track in East Sumalata District. The research method used was a field survey with a land unit approach. Data analysis to determine the type and kind of landslides is using the landslide classification index method. Analysis of geoelectric measurement results using the Schlumberger-Configuration. The results showed that the types of landslides that occurred in North Gorontalo Regency were the type of planar slide, rotational slide, slide flow, rock/topples. The average depth of the landslide slip that occurred was 5 – 15.9 meters. In general, landslides that occur in North Gorontalo Regency are caused by high rainfall and land conversion for agriculture.